Current and future lithium-ion battery manufacturing - Liu, Yangtao; Zhang, Ruihan; Wang, Jun; Wang, Yan (iScience, 2021)
Lithium-ion batteries (LIBs) have become one of the main energy storage solutions in modern society. The application fields and market share of LIBs have increased rapidly and continue to show a steady rising trend. The research on LIB materials has scored tremendous achievements. Many innovative materials have been adopted and commercialized by the industry. However, the research on LIB manufacturing falls behind. Many battery researchers may not know exactly how LIBs are being manufactured and how different steps impact the cost, energy consumption, and throughput, which prevents innovations in battery manufacturing. Here in this perspective paper, we introduce state-of-the-art manufacturing technology and analyze the cost, throughput, and energy consumption based on the production processes. We then review the research progress focusing on the high-cost, energy, and time-demand steps of LIB manufacturing. Finally, we share our views of challenges in LIB manufacturing and propose future development directions for manufacturing research in LIBs. [Display omitted] Electrochemical Energy Storage ; Industrial Chemistry ; Energy Storage ; Industrial Processing of Material ; Energy Materials